Lawmakers Order EPA To Clean Up Work Environment - Nicole Ruediger (The Scientific World Journal)
Washington, Oct 6 On Wednesday, members of Congress ordered the Environmental Protection Agency (EPA) to do a Superfund cleanup of its own work environment. For 3 hours, lawmakers and the public listened as witnesses testified to patterns of intolerance, discrimination, and retaliation within the EPA This agency is run like a 21st century plantation and this has to stop, said witness and EPA policy analyst Marsha Coleman-Adebayo.